Buletin Peternakan : PHYSIOLOGICAL STATUS, BLOOD PROFILE AND BODY COMPOSITION OF SHEEP FED WITH CA-SAPONIFIED LEMURU OIL COATED BY HERBS - Dewi Apri Astuti, Asep Sudarman (Peternakan UGM, 2015)
This study was aimed to evaluate the physiological status, blood profiles and body composition of sheep fed with Ca-saponified lemuru oil coated by herbs. Twenty fat-tailed sheep (av. BW 23Ã‚Â±1.2 kg) were used in this experiment by using Completely Randomized Design with five treatments ration and four replications of each. Sheep fed with concentrate containing 3% Ca-saponified lemuru oil and king grass (1:1) ad libitum.